1967
DOI: 10.2135/cropsci1967.0011183x000700030024x
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Seed Dormancy in Wheat (Triticum aestivum L.)1

Abstract: Seed samples of 12 wheat varieties grown in 1960 and 1961 were tested for post‐harvest dormancy under several temperature regimens at harvest time and at intervals for 80 days after harvest. Seed harvested in 1960 was tested both years. Speed and completeness of germination was expressed as a Promptness Index (PI).PI was not significantly below that of the control in any variety at 10 C germination temperature. At 20 C, all 12 varieties were dormant at harvest and this dormancy persisted from 20 to 60 days, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

1970
1970
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…This result agreed with the finding of Mares (1984) who reported that grains of nondormant varieties could germinate at 20oC in the early stages of grain-filling, while dormant varieties did not germinate at this temperature until the full-ripe stage or later. Similarly, George (1967) reported that matured grain of several varieties in the U.S. showed dormancy at 30oC but not at 10°C. The optimum temperature for germination increased after grain matured, indicating that dormancy was generally maintained until later stages of grain-filling in the varieties resistant to preharvest sprouting, while this was so only in the early stages of grain-filling at a low temperature.…”
Section: Discussionmentioning
confidence: 81%
“…This result agreed with the finding of Mares (1984) who reported that grains of nondormant varieties could germinate at 20oC in the early stages of grain-filling, while dormant varieties did not germinate at this temperature until the full-ripe stage or later. Similarly, George (1967) reported that matured grain of several varieties in the U.S. showed dormancy at 30oC but not at 10°C. The optimum temperature for germination increased after grain matured, indicating that dormancy was generally maintained until later stages of grain-filling in the varieties resistant to preharvest sprouting, while this was so only in the early stages of grain-filling at a low temperature.…”
Section: Discussionmentioning
confidence: 81%
“…or amplified (George 1967). However, lines with no sprouting resistance are expected to germinate more quickly at higher temperatures (George 1967).…”
Section: Discussionmentioning
confidence: 99%
“…However, lines with no sprouting resistance are expected to germinate more quickly at higher temperatures (George 1967). This was not observed with the Genesis water controls in the pilot experiment (Table 2) where the mean germination times were very similar at 10 and 20°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That changes do occur in seeds during storage was shown by differences in germination and seedling growth. Poor germination at 25 C of seeds from A was caused by postharvest dormancy, which is known to occur in some red wheat varieties (10,14). This type of dormancy, often referred to as "high temperature dormancy" (10,14), can be broken by germinating at a lower temperature (20 C).…”
Section: Discussionmentioning
confidence: 99%